2023
DOI: 10.1021/acsabm.3c00200
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Chiral Probe 2,3-Dihydro-4-hydroxy-chromene Schiff Base in Detecting Cu2+ Ions, l-Histidine, and Indazole: Spectroscopic Investigation and Confocal and Live Cell Imaging

Mohanasundaram Ranjani,
Vasanthakumar Keerthana,
Subramaniam Selvakumar
et al.

Abstract: 2,3-Dihydro-4-hydroxy-chromene-4(N)-ethyl thiosemicarbazone (probe F4) is used as a chemosensor, and it selectively detected Cu 2+ ions among the metal ions by showing fluorescence "TURN ON" behavior. The stoichiometric binding of the probe with Cu 2+ (CF4) was confirmed by Job's plot and mass spectroscopy. Further, CF4 was used as a sensor for the detection of L-amino acids and N-heterocyclic compounds. Among them, CF4 selectively detected L-histidine by showing fluorescence "TURN-OFF" behavior and selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Spectroscopic studies and confocal and live-cell imaging using chiral Schiff bases as probes were reported [17]. Optically active Schiff bases are also used for imaging, which is also the analysis of ( 5).…”
Section: (6) Medical or Biological Applications Of Schiff Basesmentioning
confidence: 99%
“…Spectroscopic studies and confocal and live-cell imaging using chiral Schiff bases as probes were reported [17]. Optically active Schiff bases are also used for imaging, which is also the analysis of ( 5).…”
Section: (6) Medical or Biological Applications Of Schiff Basesmentioning
confidence: 99%